Endoscopic Hernia Repair: A Novel Technique for the Repair of Inguinal Hernia in a Cadaver Model. Issue 4 (1st August 2021) - Gülaydin, Nihat; Ersöz, Feyzullah; Kalayci, Mustafa; Kara, Erdoğan
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The techniques of total extraperitoneal and transabdominal preperitoneal hernia repair have been conducted for laparoscopic repair of inguinal hernia since long. However, they offer significant disadvantages of requiring general anesthesia, producing negative cosmetic outcomes, and other serious complications. We examined the feasibility of applying an endoscopic method alternative to total extraperitoneal and transabdominal preperitoneal for laparoscopic repair of inguinal hernia in a cadaver model so as to overcome the disadvantages of the presently available techniques. Methods: A total of 4 male and 2 female cadavers [aged 18 y and above, body mass index (BMI) <40 kg/m 2 ], who were planned for a routine autopsy between January 24 and 26, 2020 were selected for the present study conducted at the Forensic Medicine Institute. Twelve laparoscopic repair surgeries of inguinal hernia were performed in 6 of these cadavers using both the inguinal areas. Results: We conducted a total of 12 surgeries on 4 male (mean age: 43.25 y; BMI: 29.05 kg/m 2 ) and 2 female cadavers (mean age: 76.50 y; BMI: 26.60 kg/m 2 ). A 7×5-cm-shaped mesh was used for both the sexes. For the fixation of the mesh, a titanium tacker was used in pubic tubercle and tendon conjoint, whereas for the fixation of ligamentum inguinale, 2/0 PDS was used in 3 surgeries, 2/0 15-cm V-Loc was used in another 3 surgeries, and titanium tacker was used in 6 surgeries. Conclusions: We demonstrated that the technique of endoscopic surgery that offers the advantages of open inguinal surgery in a cadaver model can be combined with the presently used laparoscopic intervention so as to combine all the advantages, especially for patients who are not suitable for general anesthesia, who are experiencing a recurrence after laparoscopic intervention, and who do not want any visible scares resultant from the surgery. For future studies, we suggest that the proposed technique be applied to inguinal hernia patients to ascertain clearer results.